Value-Oriented Journalism: A Pillar For Upholding Democratic Values Society - Dr. P. Shantha Bai (Educational Administration: Theory and Practice, 2023)
This paper explores the critical role of value-oriented journalism in upholding and promoting democratic values within society. It examines the principles of value-oriented journalism, including ethical reporting, accountability, transparency, commitment to truth, and public service, and their impact on public opinion, governance, and the overall democratic process. By highlighting how ethical journalism fosters informed citizenry and enhances public trust, this paper underscores the necessity of maintaining high journalistic standards for the health of democracy. Through case studies and examples, the positive effects of value-oriented journalism on policy changes, exposure of corruption, and stimulation of public debate are demonstrated. Additionally, the paper delves into the myriad challenges journalists face, such as economic pressures from declining revenues and the digital shift, political pressures including government restrictions and influence, and technological challenges like the proliferation of misinformation through social media. Using a mixed-method approach comprising surveys, interviews, and content analysis, the study provides a comprehensive understanding of the current state of journalism and the obstacles to practicing value-oriented journalism. The findings reveal a consensus among journalists on the importance of ethical practices, despite significant barriers. The study concludes by advocating for media organizations to invest in ethical training and support systems, emphasizing the need for public awareness and media literacy programs to help citizens distinguish quality journalism from misinformation, and recommending policy interventions to protect journalistic freedom and integrity. Ultimately, this paper argues that value-oriented journalism is indispensable for upholding democratic values and that continuous efforts are necessary to support ethical journalism practices in an increasingly challenging media landscape.